2008
DOI: 10.1093/rheumatology/ken182
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms within the adenosine receptor 2a gene are associated with adverse events in RA patients treated with MTX

Abstract: Objective. To examine the role of adenosine receptor 2a gene (ADORA2a) polymorphisms on outcome of MTX treatment in RA.Methods. Subjects included 309 RA patients with a defined response to MTX. Patients were included if they were (i) good responders (n = 147) (ESR <20 for >6/12 on stable dose of MTX) (ii) inefficacy failures (n = 101) (physician statement and failure to reduce ESR/CRP by 20%) or (iii) adverse event (AE) failures (n = 61) (verified by medical record review). AEs were sub-divided into gastrointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…As for rs5751876 in ADORA2A, though there is no comparable study in RA, it has been widely tested for association with other clinical phenotypes including Parkinson's disease [32], essential hypertension [27], panic disorder [26,28], and has been significantly associated with only caffeineinduced anxiety [33,34]. However, in a recent study, two intronic SNPs, rs3761422 and rs2236624, in this gene have been shown to be associated with adverse events in RA patients treated with MTX [35]. These observations together may suggest the importance of ADORA2A.…”
Section: Discussionmentioning
confidence: 99%
“…As for rs5751876 in ADORA2A, though there is no comparable study in RA, it has been widely tested for association with other clinical phenotypes including Parkinson's disease [32], essential hypertension [27], panic disorder [26,28], and has been significantly associated with only caffeineinduced anxiety [33,34]. However, in a recent study, two intronic SNPs, rs3761422 and rs2236624, in this gene have been shown to be associated with adverse events in RA patients treated with MTX [35]. These observations together may suggest the importance of ADORA2A.…”
Section: Discussionmentioning
confidence: 99%
“…No association was observed between ADORA2A and efficacy outcomes. Knowledge of the ADORA2A genotype may help to improve identification of patients at high risk of gastrointestinal toxicity with methotrexate (Hider et al, 2008).…”
Section: Receptor Polymorphisms and Disease Susceptibilitymentioning
confidence: 99%
“…We genotyped all SNPs in our own patient cohort, comprising 309 RA patients treated with MTX monotherapy and classified as good responders (n ¼ 147), inefficacy failures (n ¼ 101) (based on clinician judgment, MTX dose and measures of erythrocyte sedimentation rate and C-reactive protein) and AE failures (n ¼ 61) (AE had to be serious and lead to treatment cessation) as described in detail by Hider et al 34 to determine if they were associated with response. A pair-wise tagging SNP approach was adopted, supplemented with the two commonly investigated MTHFR SNPs from the literature.…”
Section: Study Subjects and Genotypingmentioning
confidence: 99%